Centenarian Weird Fiction from Providence in Contemporary Poland. Translational Models and the Reception of Short Stories by Howard Phillips Lovecraft – the Case Study of Dagon - Luboń, Arkadiusz (Tematy i Konteksty, 2021)
The article discusses the conventional models and translation techniques, which are most common among the Polish translators of the weird fiction by Howard Phillips Lovecraft. The proposed classification of such models, aimed at either “popularisation,” “stereotypisation” or “revision” of Lovecraft’s short stories, presents the impact of extra-textual factors (vision of the writer, target group of readers, cultural and political influences) on the content, language and style of translated works by the American author. The comparative analysis takes into consideration one of the early short stories by Lovecraft, Dagon (1917), and its Polish versions by Arnold Mostowicz (1973), Robert Lipski (1994) and Maciej Płaza (2012).